Towards a new sociological model of fiction reading. (30th July 2018) - Birdi, Briony; Ford, Nigel
Abstract : Although much previous research has considered how we read, less attention has been paid to why we read, and the influence not only of individual or text‐related factors on a reader's intention to read, but also of broader societal factors. This article presents a novel, empirically‐based model of fiction reading in a public library context, taking into account the characteristics differentiating the readers of individual fiction genres. It begins with a literature review of factors motivating a reading choice or habit, and of the effects of reading different fiction genres, before introducing three previous studies by the first author into readers' attitudes towards, and engagement with, fiction and selected fiction genres. The methodologies are then summarized both for the three previous studies and the present study. The authors present a combined analysis that integrates the findings of the previous studies in order to generate a new, evidence‐based model for the reading of fiction genres. Incorporating both demographic and motivational aspects, this model illustrates how the broad themes of the fiction reader profile interrelate, giving them a new causal ordering. Finally, there is a discussion of the implications of this work for library and information science research and practitioner communities.